Screening of Culturable Seaweed associated Bacteria with Polysaccharidases Activity Isolated from the Ambon Waters, Indonesia - Gintung Patantis; Dewi Seswita Zilda; Jiang Li Li; Xiaoqian Gu; Yuanyuan Gui; Stalis Norma Ethica (Squalen, 2023)
Seaweed is a rich source of phycocolloids, which include agar, alginate, and carrageenan. Low molecular weight polysaccharides, namely oligomers or oligosaccharides, can be produced from seaweed polysaccharides through enzymatic degradation. Most of these enzymes are produced by microorganisms closely associated with seaweed. This study aimed to isolate and select polysaccharidases-producing (SPases) bacteria associated with wild seaweed from the sea around Ambon Island, an area famous for its high marine biodiversity index. A total of 11 types of marine algae samples could be collected, and as many as 92 bacterial isolates could be cultured from all these algae samples. Screening used a clear zone method on a solid medium containing substrates agar, alginate, or carrageenan and followed by Lugol’s iodine staining solution showed that a total of 74 of the 92 bacterial isolates obtained were SPases-producing with the composition: agarase-producing (28 isolates), and alginate lyase-producing (26 isolates), and carrageenaseproducing (20 isolates). The 16S rRNA identification results showed that the 74 bacterial isolates were representative of 13 species and belong to 2 classes, namely Gammaproteobacteria and Bacillus. The bacterial isolates in the Gammaproteobacteria class obtained consisted of three genera: Pseudoalteromonas (32 isolates), Cobetia (18 isolates), and Microbulbifer (15 isolates). Bacterial isolates in the Bacillus class obtained only contain a genus consisting of 8 isolates. In conclusion, the sea around Ambon Island is a potential source of polysaccharidases-producing algal symbiont bacteria.